IMPLEMENTASI MANAJEMEN SUMBER DAYA TENAGA KEPENDIDIKAN DALAM MENINGKATKAN KUALITAS LAYANAN PENDIDIKAN DI MI MIFTAHUL HUDA SERUPA INDAH WAY KANAN LAMPUNG - Dian Puspita Sari (UNISAN JURNAL, 2024)
Endeavors to work on the nature of training administrations, one of which is by expanding the assets of schooling faculty as directors of the execution of instruction in learning exercises. This study means to decide the execution, hindering and supporting elements of instructive staff the board in working on the nature of Islamic strict schooling administrations. This kind of exploration is illustrative examination utilizing subjective examination strategies with information assortment utilizing perception, meetings, and documentation techniques then the information that has been gathered is handled and dissected with the stages, information decrease, show and end drawing. The aftereffects of the review The execution of instructive staff asset the executives in expanding the viability of Islamic Strict Training learning at MI Miftahul Huda Serupa Indah Way Kanan Lampung is very great, in particular a) at the arranging stage: instructing as per the instructive foundation, least training level S .1, gifted in utilizing learning techniques and media, b) training and improvement: including educators in overhauling and workshops, giving inspiration to proceed to advanced education levels, giving honors for exceptional instructors and assents for educators who need discipline and lackluster showing great, including instructors in each madrasa improvement, tolerating and fostering the thoughts and capability of the instructor, c) evaluation: the top of the madrasa generally leads direct oversight of the exercises of his educators, the aftereffects of educator execution appraisals are promptly followed up, and d) pay or r reward: focus entirely on privileged instructors. Supporting variables in carrying out the administration of instructive faculty in working on the nature of administrations are the help from the public authority to work on the nature of madrasa educators, the independence of schooling in madrasas and the accessibility of complete learning offices. administrations are those that emerge from educators and the execution of instructor quality improvement programs which are now and again bad.